P09 The relationship of aortic valve calcification and aortic valve area on computed tomography. (7th September 2020) - Foley, R; Lyen, S; Manghat, N; Hamilton, M
Abstract : Introduction: The quantification of aortic valve (AoV) calcification on computed tomography (CT) has been recommended for the grading of patients with aortic stenosis. We aim to characterise the relationship between AoV calcification and the aortic valve area. Methods: Data was prospectively collected on all patients undergoing CT for consideration of transcatheter aortic valve implantation (TAVI) from July 2019 - January 2020. CT was performed on multidetector scanners, (Siemens SOMATOM AS+ and Canon Aquilion ONE) and measurements of AoV calcification and AoV area were performed using validated software (TeraRecon, California). The Agatson method was used to calculate AoV calcification. Spearman correlation analysis was performed using R v3.3.3. Results: The cohort consisted of 81 consecutive patients. There were a range of AoV calcium scores from 129–7791, with a mean score of 2, 592 arbitrary units. There was a very weak negative correlation between AoV calcification and the CT derived AoV area (rs =-.08, p=0.46). Subgroup analysis demonstrated weak negative correlation in patients with tricuspid valves (n=62), rs =-.17, p=0.18 and in bicuspid valve patients (n=19), rs =-.26, p < 0.27. When AoV calcification was corrected for annulus area, there was a moderate negative correlation in tricuspid valve patients, rs =-.46, p < 0.01. Conclusion: The relationship between AoV calcification and AoV area is unclear, with no significant correlation demonstrated. It is important to understand the relationship between AoV calcification and AoV area before its use in clinical practice can be advocated.